KAJIAN KETERLIBATAN MASYARAKAT DESA HUTAN MENGEMBANGKAN SILVOINDUSTRI BIOFUEL NYAMPLUNG (CALOPHYLLUM INOPHYLLUM L) BERKELANJUTAN - Bambang Uripno; Lala M Kolopaking; R Margono Slamet; Siti Amanah (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
Energy self sufficient village program aims to improve stock and diverse energy sources and society economic opportunity. Nyamplung is very potential plant to be used as raw material of biofuel because it has very high fat content and does not use for food. The biofuel from nyamplung is a new innovation. Involvement of forest village community in biofuel industry development both as producers and consumers is very important. Forestry Research and Development Agency has established demonstration plots in Buluagung and Patutrejo villages as a facilitation in developing biofuel nyamplung silvoindustry. Up to now, the demplots still faces several problems. The survey method was used to collect data from selected 62 respondents using purposive sampling. Data were collected using questionnaires, field obsevation, and in-depth interview. Focus group discussion was used to confirm the data from the respondents. Data were analysed using rank-Spearman correlation and supported by qualitative analysis. Research results show that the demplots have not been developed through participatory approach. Involvement of community to demplots activity is low. Involvement of the village communities are significantly correlated to biofuel price, technology innovation, role of demplot and support from local leaders.